ORGANIZATIONAL BARRIERS TO IMPLEMENTATION OF INNOVATION IN GOVERNMENT INSTITUTIONS AND THE PRIVATE SECTOR. CONCEPT OF E-GOVERNMENT IMPLEMENTATION - TARASENKO, D.; NERSESSOV, V.; PAVLOVSKA, YU. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
A study of the development of modern government and commercial institutions has identified several organizational barriers to innovation. The article proposes to investigate how organizational barriers affect the application of innovations and in particular elements of e-government. Creating a concept depends on three main organizational aspects. First, the main organizational aspects that are related to the culture of the organization (control system, strategic direction, integration and coordination). Secondly, the main organizational aspects related to the structure of the organization (adaptability, involvement, integration, agreement, incentive system). Third, the main organizational aspects related to information technology (information transfer, communication, end-user orientation and employee training). The conclusion is as follows: aspects related to the understanding of organizational barriers that encourage the introduction of innovations and, in particular, elements of e-government at the level of "State" - "Business" - "Community". This study is limited to a framework that has been developed based on a review of scientific material from e-government in the theory of innovation. Now it is necessary to test this model in different contexts. This study seeks to demonstrate the key levers that hinder the factors associated with the implementation and improvement of innovation, and in particular the e-government system.